Design of direct solar PV driven air conditioner. (April 2016) - Huang, Bin-Juine; Hou, Tung-Fu; Hsu, Po-Chien; Lin, Tse-Han; Chen, Yan-Tze; Chen, Chi-Wen; Li, Kang; Lee, K.Y.
Abstract: Solar air conditioning system directly driven by stand-alone solar PV is studied. The air conditioning system will suffer from loss of power if the solar PV power generation is not high enough. It requires a proper system design to match the power consumption of air conditioning system with a proper PV size. Six solar air conditioners with different sizes of PV panel and air conditioners were built and tested outdoors to experimentally investigate the running probabilities of air conditioning at various solar irradiations. It is shown that the instantaneous operation probability (OPB) and the runtime fraction ( R F ) of the air conditioner are mainly affected by the design parameter r pL (ratio of maximum PV power to load power). The measured OPB is found to be greater than 0.98 at instantaneous solar irradiation I T > 600 W m −2 if r pL > 1.71. R F approaches 1.0 (the air conditioner is run in 100% with solar power) at daily-total solar radiation higher than 13 MJ m −2 day −1, if r pL > 3. Highlights: Design of air conditioner directly driven by stand-alone solar PV is studied. Six solar air conditioners were tested. The design parameter r pL (ratio of maximum PV power to load power) is the key. For low power loss risk, solar PV module installed must be at least three times of load power.